Konstruksi Akuntansi Insentif di Konteks Organisasi Ketenagalistrikan Jawa Tengah - Ani Setyowati; Ahmad Sahri Romadon (Universitas Budi Luhur, 2023)
The purpose of this study is to explore incentive accounting systems implemented in organizations. Incentives aimed at driving motivation to work for members of the organization cannot be separated from the accounting system because accounting provides a real picture of the effectiveness of the allocation of resources managed by the company. This type of research is qualitative research with a case study approach. The focus of the research is carried out in companies that operate in electricity services in the Central Java region. The information gathering method was carried out using a semi-structured interview model addressed to a number of managers and employees in the company. The results of the study found that incentive accounting applied in companies was effective in helping organizational leaders and members to optimize the management of financial resources in companies. With the existence of incentive accounting, companies can allocate financial resources to direct members of the organization to be more professional at work and responsible for carrying out work procedures.